Analisis Thumbnail Video dalam Meningkatkan Retensi Pengguna Youtube Melalui Pendekatan Desain Grafis yang Inovatif - wibowo, khalaya azizah; Widyasari Widyasari (Lembaga Pengembangan Kinerja Dosen, 2023)
In the accelerating digital age, video thumbnails have become an important element in attracting users' attention and encouraging further interaction. Video thumbnails play an important role as a visual attraction to attract the audience. Graphic design strategies focus on elements such as creativity, color, typography, and illustration to create interesting and informative video thumbnails. Experimental research methods are used to test the effectiveness of new video thumbnail designs in improving user retention. This research focuses on improving YouTube user retention through the introduction of an innovative graphic design approach to video thumbnails. Research results show that an innovative graphic design approach can significantly improve YouTube user retention, demonstrating the importance of the role of graphic design in the context of digital marketing and social media user interactions. This study contributes significantly to the practice of graphic design and digital marketers in optimizing the user experience through interesting and informative video thumbnails.